(untitled) (Global Journal of Science Frontier Research, 2021)
Plants are the source of a great variety of phytochemicals, the valuable properties of which have been utilized by human being for centuries ever since the dawn of human civilization. Man has employed therapeutic plants as the greatest bio-resource of remedies for folk and contemporary treatments. Most plant species used as folklore medicine are claimed to retain the capacity to cure or mitigate some health disorders. Cleome rutidosperma has been reported for treatments as anti-inflammatory, antimicrobial, etc. agents. The present investigation was aimed to explore the phytoconstituents of the ethanolic and n-hexane extracts of the entire plant of Cleome rutidosperma employing the GC-MS technique. The extracts were analyzed with Thermo-Finnigan Trace GC Ultra (Waltham, MA, USA) equipped with a splitless injector, coupled to an ion trap mass spectrometer (MS) (Polaris Q) coupled to a Xcalibur data software processor.